1957
DOI: 10.1152/ajplegacy.1957.191.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Aphagia in Chickens

Abstract: Aphagic chickens have been produced with electrolytic lesions placed stereotaxically in the diencephalon. These chickens were maintained by introducing food into their crops through a tube. They were inactive and lost much of the ‘nervous’ temperament of White Leghorn chickens. One or more of these chickens showed additional disturbances: impaired gastrointestinal motility, temperature regulation, adipsia and abnormal body composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1959
1959
1999
1999

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…At present, however, several lines of evidence suggest that the avian brain, particularly the hypothalamus, contains important thermal integration and control centers. Lesions in the anterior hypothalamus disrupt thermoregulation in domestic fowl (Rogers and Lackey 1923;Feldman et al 1957;Lepkovskyet al 1968) and house sparrows (Mills and Heath 1972b). Rautenberg et al (1972) found that although the lower cervical and thoracic spinal cord in the domestic pigeon is sensitive to local heating and cooling, appropriate thermoeffector responses depend on neural information ascending to higher centers.…”
Section: Integration Of Sensory Input and Control Of Effectorsmentioning
confidence: 99%
“…At present, however, several lines of evidence suggest that the avian brain, particularly the hypothalamus, contains important thermal integration and control centers. Lesions in the anterior hypothalamus disrupt thermoregulation in domestic fowl (Rogers and Lackey 1923;Feldman et al 1957;Lepkovskyet al 1968) and house sparrows (Mills and Heath 1972b). Rautenberg et al (1972) found that although the lower cervical and thoracic spinal cord in the domestic pigeon is sensitive to local heating and cooling, appropriate thermoeffector responses depend on neural information ascending to higher centers.…”
Section: Integration Of Sensory Input and Control Of Effectorsmentioning
confidence: 99%
“…and satiety centres (Feldman et al, 1957;Smith, 1969). However infusion techniques, as used in the mammal, such as the introduction of phloridzin and gold thioglucose into these hypothalamic areas, have no effect on chickens (Svacha and Reid, 1973;Apostol et al, 1977).…”
Section: T G H Shurlock and J M Forbesmentioning
confidence: 99%
“…In contrast, bilateral removal of the LHy results in aphagia and a marked loss in body weight (Anand and Brobeck, 1951). The experimental results found using mammals have been confirmed with avian species (Feldman et al, 1957;Lepkovsky and Yasuda, 1966;Kuenzel and Helms, 1967;Kuenzel, 1972Kuenzel, , 1982aSnapir et al, 1973;Sonoda et al, 1975). Since the 1950's, research has been committed to Scientific Article Number A-4821 Contribution Number 7847 of the Maryland Agricultural Experiment Station (Department of Poultry Science).…”
Section: Introductionmentioning
confidence: 86%